2018
DOI: 10.1002/2017ms001243
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Processes of the Tropical Intraseasonal Variability Simulated in an Aqua‐Planet Experiment: What is the Intrinsic Mechanism for MJO Onset?

Abstract: To understand the intrinsic onset mechanism of the Madden‐Julian Oscillation (MJO), we simulated a set of initiation processes of MJO‐like disturbances in 10 year aqua‐planet experiments using a global atmospheric model with a 56 km horizontal mesh and an explicit cloud scheme. Under a condition with a zonally nonuniform sea surface temperature (SST) in the tropics, we reproduced MJO‐like disturbances over the western warm pool region. The lagged‐composite analysis of detected MJO‐like disturbances clarifies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
(167 reference statements)
2
14
0
Order By: Relevance
“…Figures d and S3b show that the midtropospheric equatorial IO has positive horizontal advective tendencies mainly by cross‐equatorial flows from off‐equatorial humid regions (e.g., 0–10°N, 60–80°E) associated with MRG shallow circulations or broadening of moistened areas around the IO. This is consistent with a preconditioning process in the aqua‐planet MJO study by Takasuka et al ().…”
Section: Impacts Of Mrgs On the Mjo Initiation And Propagationsupporting
confidence: 91%
See 3 more Smart Citations
“…Figures d and S3b show that the midtropospheric equatorial IO has positive horizontal advective tendencies mainly by cross‐equatorial flows from off‐equatorial humid regions (e.g., 0–10°N, 60–80°E) associated with MRG shallow circulations or broadening of moistened areas around the IO. This is consistent with a preconditioning process in the aqua‐planet MJO study by Takasuka et al ().…”
Section: Impacts Of Mrgs On the Mjo Initiation And Propagationsupporting
confidence: 91%
“…The proposed mechanism covers a classical view that MJO convection comprises westward convective disturbances (Nakazawa, 1988) and insights from the long-term aqua-planet simulation (Takasuka et al, 2018). The next step is to examine the roles of MRGs in MJO mechanics in observation and numerical studies for more realistic cases.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By examining the third MJO event during the DYNAMO period as observed in December 2011, Kubota et al (2015) found the advective pre-moistening effect of the westward-propagating disturbances with a 2-day period, which is consistent with the findings of Yu et al (2018). More recently, using the in situ observation collected during the Year of Maritime Continent (YMC)-Sumatra 2017, Takasuka et al (2019) found evidently westward-moving positive moisture and meridional wind disturbances of the quasi-3-8-day mixed Rossby-gravity waves preceding the onset of the December primary MJO event, validating their earlier findings using the aqua-planet experiments in Takasuka et al (2018).…”
Section: Introductionsupporting
confidence: 85%